Sistem Informasi Geografis Berbasis Mobile Rekomendasi Pencarian Iklan Dan Petunjuk Arah Lokasi Transaksi Pada Aplikasi Jual Beli Online Menggunakan Location Based Services - Wildan Afif Abidullah; Issa Arwani; Muhammad Tanzil Furqon (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
E-commerce is a method of selling, purchasing and marketing goods and services through electronic media such as radio, television and computer or internet network. Otomotifstore.com is one of the e-commerce or online shop sites in the automotive field with the concept of bringing together between sellers and buyers. Buyers who want to buy something will search for ads based on their location, which then the buyer will contact the seller to make the transaction. The solution that can ease the transaction process based on the nearest location is to create an application that can provide advertising recommendations in the form of geographic maps based on the location of the buyer followed by route to reach the location of transaction. The application is built based on android mobile using Location Based Services with a Global Positioning System (GPS) which can take the target of prospective buyers and sellers location. The geographic map displayed in the apps is by utilizing the android API maps from google. The application can ease the sellers and buyers to make transactions directly by the presence of ad distribution in the form of geographic maps and followed by route to transaction location. Based on the validation testing, the application have fulfilled all the functional requirements and usability testing proves that the built application has been successful with a percentage of 97%, so the application is ready to used for user. From the results of compatibility testing of three types of devices with different specifications obtained valid results.